Bronchoscopy for Removal of Foreign Body in Lower Airway: A Retrospective Analysis - Ramasundram, Shankar; Kuppusamy, Sharmini; Kumarsamy, Sivakumar; Ambu, Valuyeetham Kamara; Mohamad, Irfan (Bangladesh Journal of Medical Science, 2019)
Bronchoscopy is performed for diagnostic or therapeutic purpose. Therapeutic bronchoscopy is mainly done for removal of foreign body from lower airway. Both the condition and procedure itself are associated with high mortality and morbidity. The aim of the study was to audit data regarding demography, types and location of foreign body, onset of symptom, admission duration, clinical and investigation findings along with duration of ventilation. We also highlight on the complications pertaining to the condition in our series. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.779-782